Melhoria da comunicação e do relacionamento entre o governo e os cidadãos com aplicativos móveis: o caso do m-government do estado de São Paulo - Andrade, Maurício Arantes de (2015)
This research has the goal of exploring how the São Paulo State government can use technology to get the State closer to citizens by means of mobile applications. The increase in use of mobile applications by Brazilian people and recent broadening in use of m-government as an effort in search of better services to São Paulo State citizens in last two decades have set the scenario in which was created the Request for Proposal of Citizens’ Technology and Services Agency of Government Department of São Paulo State. In this work, there was integration of different research methods: literature review, semi-structured interviews with important players for policy formulation, assessment of São Paulo State mobile application policy and assessment of its applications, benchmarking of international experience and analytic diagnostic of current situation. It was found as strengths the existence of an Agency close to Governor, the creation of a central application which references the other applications from government and the existence of a government technology company with the skills to develop services and applications. As challenges, it was identified applications communication and promotion strategy, lack of legislation about m-government and lack of public policy and consistent strategic plan to guide improvements and reaching of results with speed and efficiency. It is recommended that: 1) Citizens’ Technology and Service Agency act as central body to generate guidelines to m-government, beyond e-government issues, 2) that government focuses on aiming services toward citizens and not mainly to applications development, and 3) that a clear policy to m-government diffusion be formulated and implemented in a way it can be understood and replicated by all government players and pervade all direct and indirect administration bodies, not restricting to IT departments. The conclusion is that m-government approach in Brazil is still incipient, requiring additional academic research to consolidate critical mass about the subject. We consider that this subject will have attention and investment from government in the next years. São Paulo State is in a good direction, but to advance effectively state managers will have to incorporate best practices from international experience in m-government, having a long way to effectively provide a better relationship between the State and citizens by the use of mobile applications, with approach of unique government to unique citizen.